Naruto. Vol. 20, Naruto vs. Sasuke - Kishimoto, Masashi, 1974-; Yamazaki, Joe (Shonen Jump manga., 2007)
Sakura is caught in the battle between Naruto and Sasuke. Naruto and Sasuke fight against each other as they move toward separate destinies.